Measuring Attitudes About Alcohol Misuse and Dependence Among Alaska Native People Within a Tribal Health Care System. Issue 1 (27th January 2023) - Dillard, Denise A.; Hebert, Luciana E.; Shaw, Jennifer L.; Trinidad, Susan B.; Dirks, Lisa G.; Lillie, Kate; Ludman, Evette J.; Donovan, Dennis; Burke, Wylie
Abstract : Objectives: Attitudes about alcohol misuse and dependence influence alcohol use and help-seeking behavior. Alaska Native and American Indian (AN/AI) people have higher rates of alcohol-related morbidity and mortality but engage in treatment at lower rates than the general population. No validated instruments exist to assess attitudes of AN/AI people about alcohol misuse and dependence to inform treatment and prevention efforts. This study aimed to develop an instrument to assess public attitudes among AN/AI people of alcohol misuse and dependence. Methods: This multiphase, mixed-methods study was conducted at Southcentral Foundation, a tribally owned health system serving 65, 000 AN/AI people in Alaska. We conducted focus groups and interviews with health system users, providers, and leaders to adapt the Public Attitudes About Addiction Survey. The adapted instrument was piloted with 200 people. Cognitive interviews and exploratory and confirmatory factor analyses were used to refine the instrument, which were then administered to 777 AN/AI people. Results: Initial exploratory factor analysis identified 5 factors, including 3 from the original Public Attitudes About Addiction Survey (moral, disease, nature), a combined psychology and sociology factor (psychosocial), and a new factor (environment). A final 4-factor model (psychosocial, moral, disease, nature) with 14 items had good fit with root mean square error of approximation (0.035; comparative fit index = 0.977; Tucker-Lewis index = 0.970; standardized root mean residual = 0.040) and loadings ranging from 0.41 to 0.80. Conclusions: This study developed the first instrument to assess AN/AI attitudes about alcohol misuse and dependence. This instrument has potential to inform alcohol-related treatment in AN/AI communities. Future research is warranted to adequately measure place-based contributors salient to AN/AI people.